Analisis Kriminal Santet Sebagai Salah Satu Tindak Pidana Sesuai Dengan Perspektif Hukum RUU-KUHP di Indonesia - Priambodo, Rodrigo; Nugroho, Widhi Cahyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In overcoming a criminal problem, we will usually refer to the legal perspective of the Criminal Code Bill in Indonesia. This is because the existence of a case that causes victims and even causes death must be a serious problem in the law of the Draft Criminal Code. However, in this research the author will discuss the analysis of criminal cases caused by black magic which lead to the criminal act of the Criminal Code Bill in Indonesia. In fact, in cases of criminal acts that have existed in Indonesia so far, a judge has never given a decision for the criminal of black magic, this is due to the lack of authentic evidence related to proving that someone who is a victim of black magic actually exists. This has caused debate among all legal experts, plus several years ago the law that was passed according to the Draft Criminal Code was a law that discussed witchcraft as a criminal act whose punishment was already written in the Draft Criminal Code in Indonesia. In the debate itself, there were pros and cons to the decision submitted to the Supreme Court in ratifying the law, because one of the main factors from several legal experts who were against the ratification explained that if the evidence obtained is not accurate, how can we determine the perpetrator or victim in the matter. In this research, the type of research used in this thesis is normative research. This research method is used to determine legal rules, legal principles, and legal doctrines in order to answer the legal issues faced. This type of normative research is also often referred to as doctrinal research.